Granulocyte‐reactive antibodies are associated with red blood cell alloimmunization. Issue 2 (8th April 2014) - Schönbacher, M.; Heinzl, M. W.; Dauber, E.‐M.; Mayr, W. R.; Panzer, S.; Körmöczi, G. F.
<x xml:space="preserve">Abstract</x> Granulocyte‐reactive antibodies may cause transfusion‐related acute lung injury (TRALI) and immune neutropenias. Risk factors for their acquisition other than previous alloexposition are largely unknown. In addition to the known association between human leucocyte antigen alloantibodies and red blood cell alloimmunization in selected cohorts of transfused patients, this study investigated a possible extension of this association to granulocyte‐reactive antibodies in women with a history of pregnancy. The overall prevalence of granulocyte‐reactive antibodies in 333 samples from women with a history of pregnancy (143 samples containing red cell alloantibodies) was 23·1%. The prevalence in the red cell‐alloimmunized group (32·9%) was significantly higher than in controls (15·8%, P < 0·001). This could suggest that some individuals may be strong immunological responders, forming alloantibodies more readily than others.